2019
DOI: 10.3390/pharmaceutics11100491
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Dynamic Dissolution of Electrospun Polymeric Nanofibers Loaded with Piroxicam

Abstract: We investigated and monitored in situ the wetting and dissolution properties of polymeric nanofibers and determined the solid-state of a drug during dissolution. Piroxicam (PRX) was used as a low-dose and poorly-soluble model drug, and hydroxypropyl methylcellulose (HPMC) and polydextrose (PD) were used as carrier polymers for electrospinning (ES). The initial-stage dissolution of the nanofibers was monitored in situ with three-dimensional white light microscopic interferometry (SWLI) and high-resolution optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Another fiber-based system using hydroxypropyl methylcellulose and polydextrose was developed for Px release. 30 They observed that the recrystallization of Px in a microcrystalline form instantly after wetting could result in higher drug dissolution. All of these studies rely on using a polymer carrier to develop a drug delivery system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another fiber-based system using hydroxypropyl methylcellulose and polydextrose was developed for Px release. 30 They observed that the recrystallization of Px in a microcrystalline form instantly after wetting could result in higher drug dissolution. All of these studies rely on using a polymer carrier to develop a drug delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the hydrophilic nature of the components, the total release of Px took less than 2 min. Another fiber-based system using hydroxypropyl methylcellulose and polydextrose was developed for Px release . They observed that the recrystallization of Px in a microcrystalline form instantly after wetting could result in higher drug dissolution.…”
Section: Introductionmentioning
confidence: 99%
“…The PRX-loaded nanofibers exhibited a quasi-dynamic dissolution via recrystallization. SWLI enabled a rapid, non-contacting, and non-destructive method for in situ monitoring of the early-stage dissolution of nanofibers and regional mapping of crystalline changes during wetting [6].…”
mentioning
confidence: 99%